Sustainable Cutting Process For Milling Operation Using Disturbance Observer - Zamberi, Jamaludin; Jailani, Jamaludin; Chiew, Tsung Heng; Abdullah, Lokman; Rafan, Nur Aidawaty; Maharof, Madihah (Elsevier B.V., 2016)
This paper focuses on design of disturbance force observer for sustainable machining process in milling application. In milling process, cutting force acts directly on work surfaces thus producing external impact on the drives system of the positioning table. This effect must be compensated in order to preserve accuracy and quality of the final product, thus creating a sustainable machining process. Disturbance force observer (DFO) is a type of estimator that estimates precisely the disturbance force with prior knowledge of the cutting force harmonics frequencies. This paper presents both numerical and experimental results of DFO performed on an XYZ positioning milling table using measured cutting force. Four control configurations were considered; PID, cascade P/PI, PID with inverse model based disturbance observer, and PID with DFO. The FFT tracking error analysis showed that a near complete compensation of the disturbance force at identified harmonics frequencies was achieved.